Diversions of the Ribeira River Flow and Their Influence on Sediment Supply in the Cananeia-Iguape Estuarine-Lagoonal System (SE Brazil) - Cornaggia, Flaminia; Jovane, Luigi; Alessandretti, Luciano; Alves de Lima Ferreira, Paulo; Lopes Figueira, Rubens C.; Rodelli, Daniel; Bueno Benedetti Berbel, Gláucia; Braga, Elisabete S. (Frontiers in Earth Science, 2018)
The Cananéia-Iguape system is a combined estuarine-lagoonal sedimentary system, located along the SE coast of Brazil. It consists of a network of channels and islands oriented mainly parallel to the coast. About 165 years ago, an artificial channel, the Valo Grande, was opened in the northern part of this system to connect a major river of the region, the Ribeira River, to the estuarine-lagoon complex. The Valo Grande was closed with a dam and re-opened twice between 1978 and 1995, when it was finally left open. These openings and closures of the Valo Grande had a significant influence on the Cananéia-Iguape system. In this study we present mineralogical, chemical, palaeomagnetic, and geochronological data from a sediment core collected at the southern end of the 50-km long lagoonal system showing how the phases of the opening and closure of the channel through time are expressed in the sedimentary record. Despite the homogeneity of the grain size and magnetic properties throughout the core, significant variations in the mineralogical composition showed the influence of the opening of the channel on the sediment supply. Less mature sediment, with lower quartz and halite and higher kaolinite, brucite, and franklinite, corresponded to periods when the Valo Grande was open. On the other hand, higher abundance of quartz and halite, as well as the disappearance of other detrital minerals, corresponded with periods of absence or closure of the channel, indicating a more sea-influenced depositional setting. This work represented an example of anthropogenic influence in a lagoonal-estuarine sedimentary system, which is a common context along the coast of Brazil.